Percutaneous Nephrolithotomy Success Rate and Complications in Patients with Previous Open Stone Surgery - Khorrami, Mohammadhatef; Hadi, Mazaher; Mohammadi Sichani, Mehrdad; Nourimahdavi, Kia; Yazdani, Mohammad; Alizadeh, Farshid; Izadpanahi, Mohammad-hosein; Tadayyon, Farhad (Urology Journal, 2014)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:Arial; –> <!–[endif] –> Abstract Purpose: To determine the effect of previous single or multiple open stone surgeries on percutaneous nephrolithotomy (PCNL) results and complications. Materials and Methods: We reviewed medical records of 1422 patients who had been undergone PCNL in our institute between 1998 and 2011 by the same surgeon. Patients were divided into 3 groups. The first group included patients with no history of previous ipsilateral open stone surgery (n = 711). Patients in second group had been undergone only one open stone surgery before PCNL (n = 405) and patients with more than one previous open stone surgery were placed in third group (n = 306). We compared operation duration, stone free rate (SFR), number of attempts to access the collecting system and intraoperative and postoperative complications between 3 groups. Results: There were no differences in sex, body mass index, stone burden and laterality between 3 groups. Operation time was significantly shorter in the first group (P = .000) while there was no statistically significant differences in operation duration between second and third groups (P > .973). The number of attempts to enter the collecting system was significantly lower in the first group in comparison to other two groups (P = .00). We didn’t find significant differences between 3 groups in hospital stay, SFR, intraoperative and postoperative complications. Conclusion: Our findings demonstrated that PCNL can be performed in patients with one or more open stone surgery history successfully without further complications.